Katip Çelebi'de Islahat Düşüncesi - (:unkn) unknown (My University, 2007)
Kâtip Çelebi, Osmanlı devletinde ortaya çıkan siyasi, sosyal ve ahlaki bozulmaları tespit etmek ve bu sıkıntıları çözmeye yönelik ıslahat tedbirlerini önermek amacıyla birçok eser kaleme almıştır. İşte bu çerçevede olmak üzere araştırma, Kâtip Çelebi'nin bozulmaya hangi verilerden hareketle ulaştığını, bozulmayı nasıl algıladığını ve en önemlisi de bu bozulmaya karşı ne tür bir ıslahat önerdiğini tartışmak istemektedir.

Kâtip Çelebi, has written a number of books to determine political, social and moral corruption which arose in the Ottoman Empire and to propose reform measures for the solution of those problems. This study is triying to discuss that from which data Kâtip Çelebi had reached to the conclusions about corruption, how he understood the corruption, and above all, what sort of proposals he offered for the correction of that correption, with reference to his works.
Reformist Thought in the Works of Katip Çelebi
Keywords: Antropoloji; Kültürel Çalışmalar; Folklor; Tarih